A Modern Method for Analyzing Related Substances of Cabotegravir and Rilpivirine Using RP-HPLC, along with the Characterization of their Degradation Products Via LCMS - Gudela, Krishnaveni (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: The estimation, separation, and validation of Cabotegravir and Rilpivirine along with their impurities were performed using the RP-HPLC technique. Materials and Methods: Cabotegravir, Rilpivirine, and their respective impurities were separated on an Inertsil ODS column (150 × 4.6 mm, 3.5 μ) using a mobile phase consisting of 5 mM Ammonium Formate and acetonitrile at a flow rate of 1 mL/min at room temperature. The PDA detector from a Waters HPLC e-2695 quaternary pump was used with a wavelength of 231 nm. The linearity was investigated for 17 min with injection concentrations of 75–450 μg/mL of Rilpivirine, 50–300 μg/mL of Cabotegravir, and 1.25–7.5 μg/mL of each impurity of Cabotegravir and Rilpivirine. The validity of the proposed method was verified using the International Conference on Harmonization (ICH) guidelines. Results and Discussion: The results of method validation including specificity, linearity, accuracy, ruggedness, and robustness were within the permissible range. Conclusion: The HPLC-MS technique successfully validated the chemical structures of the degradation products of Cabotegravir and Rilpivirine, and stress studies were carried out in compliance with ICH Q2 (R1) guidelines